The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/ca.22824
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anatomy and surgical significance of the lingual foramina and their canals

Abstract: The lingual foramina and canals can be categorized as median or lateral based on their relation to the midline of the mandible. Investigation of the mandibular lingual region is often done with gross anatomical dissections of cadavers, 2D panoramic radiographic imaging, CT, and cone beam CT (CBCT). While gross studies are the most reliable at qualifying canal contents and course, CBCT proved to be superior to other radiographic techniques for visualizing lingual foramina and canals. The submental and sublingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 52 publications
0
31
0
3
Order By: Relevance
“…The mental artery that emerges from the mental foramen is very small and does not play any significant role in providing blood to the chin. The mental artery may be able to receive blood from the labiomental artery when the inferior alveolar artery is partially occluded and the blood supply to the central area of the mandibular teeth is insufficient …”
Section: Discussionmentioning
confidence: 99%
“…The mental artery that emerges from the mental foramen is very small and does not play any significant role in providing blood to the chin. The mental artery may be able to receive blood from the labiomental artery when the inferior alveolar artery is partially occluded and the blood supply to the central area of the mandibular teeth is insufficient …”
Section: Discussionmentioning
confidence: 99%
“…There are two groups of LF differentiated by their location on the mandible, that is, the median lingual foramen (MLF) and lateral lingual foramen (LLF: Figs. ) (He et al ). The MLF is located usually on the mandible's midline, whereas the LLF is in the canine or premolar area largely (Tagaya et al ; Kim et al ; Yildirim et al ; Sanomiya Ikuta et al ).…”
Section: Literature Review and Suggestions For Risk Assessment Of Injurymentioning
confidence: 99%
“…Cadaveric studies of the dry mandible and clinical studies using CBCT have found consistently that up to 99% of individuals had the MLF (McDonnell et al ; von Arx et al ; He et al ).…”
Section: Literature Review and Suggestions For Risk Assessment Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Cone‐beam computed tomography (CBCT), which is often required in daily practice, gives oral and maxillofacial surgeons much morphological information about hard tissue. During the past decade, many anatomical and radiological studies using CBCT have been published (Kalender et al, ; Park and Lee, ; Wang et al, ; Ciftci et al, ; He et al, ; Iwanaga et al, ) and three‐dimensional images have enabled us to understand details of surface anatomical structures such as the location of accessory foramina and the running course of canals inside the bones. However, no methods for studying the bone canal without radiography have been established, and endoscopy could be a new method for observing the canal walls.…”
mentioning
confidence: 99%